El regreso del experimentador y la metodología de la apertura de las cajas negras - Armero Sanjosé, Julio César (ENDOXA, 2005)
The experimenter’s regress is one of the arguments that seem to back epistemológical relativism. It has been noted that it carries a cióse resemblance to the hermeneutical circle. This paper tries to show how the hindrances for scientific practice involved in the situation described by the argument appear in unrelated áreas of research and how the difficulties are dealt with. The comparative approach seems to throw some light on a few features of baconian science often made dependent upon wide sociological fact.